Performance investigation and multi-objective optimization of end milling of aluminium alloy 6061 T6 with coated and uncoated carbide tools under various cooling conditions - Syeda Najiha, Masood (2015)
Application of cutting fluids as cooling and lubricating media is considered essential in manufacturing practices on account of providing lubrication, heat transfer capabilities, corrosion minimization as well as flushing away of metal chips and debris. On account of sizable costs, increasing eco-awareness, implementation of sustainability indices in manufacturing units and strict regulations due to detrimental effects of cutting fluids to the environment and the human exposure, economically viable substitutes to cutting fluids are being explored. Minimum quantity lubrication (MQL) technique offers a near-term solution to the problem. The objectives of this study are to investigate the machining performance and to develop multi-objective optimization model in end milling of aluminium alloy AA6061-T6 with conventional MQL and nanofluid-MQL techniques. Uncoated tungsten carbide (WC-Co 6.0%) and PVD TiAlN and TiAlN+TiN coated carbide cutting tools are considered using 23.4-54.0 ml/hr flow rate of commercial mineral oil for MQL machining with different combinations of input cutting parameters. Nanofluid % volume fraction is varied from 0.5 %-4.5 %. Response surface methodology (RSM) with central composite design approach is used for the design of experiments. Second order mathematical models are developed for machining performance measures with different cooling conditions and validated statistically. The developed models show good agreement (< 5 % error) with the experimental results. PVD coated carbide tools outperformed uncoated tool in terms of tool damage and surface quality and uncoated tool is selected for the nanofluid MQL machining. The effectiveness of MQL is compared with conventional flooded conditions. Nanofluid-MQL exhibits superior performance compared to flooded and conventional MQL in terms of surface roughness and tool wear. For material removal rate results are almost similar in all cases. Tool damage is characterized by SEM micrographs and EDX patterns. Adhesion, edge chipping and coating damage for uncoated and coated tools are observed with higher feed rate, higher depths of cut and lower MQL flow rate. The major benefit from the water-based nanofluid MQL is shown in the edge integrity, which is attributed to the cooling effect produced due to latent heat of vaporization of water. Experimental results show the prospective utilization of water-based TiO2 nanofluid as MQL cooling medium. Comprehensive multi-objective optimization model using genetic algorithm is developed to optimize machining performance measures under different MQL conditions, based on Pareto optimal design approach. As a result of optimization, the resultant improvements in surface roughness and flank wear in conventional MQL machining for uncoated tungsten carbide tool are 74.2 % and 58.4 %; for PVD TiAlN coated tools are 16.9 % and 73.6 %; for PVD TiAlN+TiN coated tool are 60 % and 41.4 %, respectively. For nanofluid-MQL machining, the optimum nanofluid volume concentration is 2.64 %. Promising results of the study in terms of process performance, compared with traditional practices, highly advocate the use of MQL technique with water-based nanofluid in industrial machining application as well as academia activities.